Ectopia cordis: A case report of pre-surgical care in resource-limited setting. (June 2021) - Lodhia, Jay; Chipongo, Hillary; Chilonga, Kondo; Mchaile, Deborah; Mbwasi, Ronald; Philemon, Rune
Abstract: Introduction and importance: Ectopia cordis is a rare congenital malformation of thoracic midline fusion that presents as location of the heart outside the open chest cavity. This presents as a surgical emergency and demands early and specialized intervention. Particularly in resource-limited settings, where prenatal ultrasonography screening is not done, these children are often born in facilities without the capability of managing such conditions definitively, necessitating them to be referred to a specialized centre. At lower health facilities, the challenge is in ensuring that the child is kept stable and protected from infection until they can reach a centre with the facilities required for care. This report describes the management give to such a child until they were successfully handed over to a cardiac institute. Case presentation: We present a newborn male baby delivered at term to a mother from a low socio-economic background with his heart and abdominal viscera outside the thoracic and abdominal cavity. Despite presenting at a centre without cardiac surgery facilities or cardiologists, they were sustained until referral. Clinical discussion: Ectopia cordis is a rare congenital anomaly characterized by defect in the fusion of the anterior chest wall resulting in the abnormal extra-thoracic location of the heart. Five types exist; cervical type with worst prognosis, attempts can be made to re-locate the heart and close the thoracic defect surgically. Conclusion: Even with limited resources, it is possible to provide the basic care necessary to sustain a child with this complex anomaly until definitive management can be provided. Highlights: Ectopia cordis is a rare congenital anomaly characterized by an abnormal extra-thoracic location of the heart. Diagnosis can be made by prenatal ultrasonography or MRI hence aid in planning the pregnancy outcome. Surgical relocation is the management; prognosis depends on the type.